Promoting Creative and Aesthetic Thinking in Fine Arts Education: Innovative Strategies - Sayfiyeva Ozoda Madamin qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article examines innovative strategies for promoting creative and aesthetic thinking in fine arts education. It highlights the significance of project-based learning, interactive lessons, and digital tools in enhancing students’ visual perception, artistic evaluation, and overall engagement with art. The study emphasizes the importance of student-centered pedagogy and the creation of a supportive learning environment as essential factors for developing students’ creativity and aesthetic awareness.